Synthèse et caractérisation physicochimique des oxydes de structure spinelle - Hammouche, Jannat (جامعة الوادي - University of Eloued, 2022)
In summary, ZFO nanocomposites with varying Ni dopants were successfully synthesized using auto-combustion followed by the annealing process. XRD revealed the formation of zinc ferrites crystallites with cubic spinel structure. The morphology of different zinc ferrites was evaluated using SEM. The degradation rate of MB solution increases successively with Ni doping up to 30% and thereafter decreases. With an optimum Ni doping (30%), photocatalytic activity up to 98% was achieved with as-synthesized ZFO nanocomposites, which can perform as an environmentally friendly, easily isolable, and recyclable photocatalyst for water treatments. Moreover, the non-annealed YFO nanomaterials with varying Cu dopants were successfully synthesized using the auto-combustion process. XRD revealed the formation of Yttrium ferrites crystallites with orthorhombic Perovskite structure. The morphology of different YFO nano-oxides was evaluated using SEM. The degradation rate of MB solution was investigated under UV and Visible light and the highest degradation efficiency was 95% for 20% Cu doping percentage. The reusability of the photocatalyst was achieved up to the third cycleباختصار، تم توليف مركبات (YFO) النانونية بنجاح و ذلك بإضافة نسب متفاوتة من النيكل باستخدام تفاعل الاحتراق الذاتي متبوعا بعملية التلدين. تم التحقق من تشكل بلورات زنك الحديد ذات الهياكل المكعبة الورانية عن طريق (XRD). و كذلك (SEM) كشف لنا مختلف البنيات المتواجدة في (ZFO). سرعة تحلل محلول أزرق البروموتيمول ازدادت بنجاح مع ازداياد نسبة إضافة النيكل حتى ٣٠٪ و بعدها نقصت. تم التأكد من نشاط التحليل الكهروضوئي حتى نسبة ٩٨٪ بالنسبة ل٣٠٪ من النيكل المضاف إلى المركبات النانونية ل (ZFO) و التي تم تحضيرها كي تكون كمواد صديقة للبيئة، سهلة العزل، و يمكن إعادة تدويرها لمعالجة المياه. علاوة على ذلك، تم توليف مواد نانونية (YFO) بتراكيز مختلفة من عنصر النحاس باستخدام عملية الاحتراق الذاتي بدون تلدين. تم التحقق من تشكل بلورات إيتريوم الحديد ذات هياكل البيروفسكيت الأورثورمبية ب(XRD). و (SEM) قيمت شكل مختلف بنيات (YFO). تم دراسة سرعة تحلل محلول أزرق البروموتيمول تحت الضوء فوق البنفسجي و الضوء المرئي، و أعلى كفاءة تحلل كانت ٩٥٪ لنسبة ٢٠٪ من النحاس المضاف. تم النجاح في إعادة استخدام المحفز الضوئي حتى المرة الثالثة.
Synthesis and Physicochemical Characterization of ZnFe2-xNixO4 & Y1-xCuxO3 for photocatalysis application
Analytical electrochemistry and environment:أطروحة دكتوراه في العلوم الدقيقة تخصص
Keywords: :. ZFO, YFO, Ni-doped, Cu-doped, photocatalysis, photocatalyst MB, nanomaterials; أكسيد زنك الحديد، أكسيد إتيريوم الحديد، إضافة النيكل، إضافة النحاس، التحليل الكهروضوئي، محفز التحليل الضوئي، أزرق البروموتيمول، المواد النانوية